San Severino Marche Smart Grid Pilot within the InteGRIDy project. (November 2018) - Falabretti, D.; Moncecchi, M.; Mirbagheri, M.; Bovera, F.; Fiori, M.; Merlo, M.; Delfanti, M.
Abstract: This paper reports the presentation of a Smart Grid architecture designed with respect to the actual Italian scenario and ongoing to be experimentally validated in the distribution grid of San Severino Marche Pilot, Italy. The main characteristics of the smart grid architecture deployed are discussed and two of its innovative functionalities are detailed: reconfiguration of the Medium Voltage (MV) grid and Energy Storage Systems (ESSs) exploitation for the ancillary services provision. Such functionalities are introduced from both a theoretical and an experimental point of view. Data collected from the field have been processed by means of mathematical models in order to achieve a quantitative evaluation of the performances. Results are related to the energy losses improvement the DSO could obtain thanks to a MV grid reconfiguration and to the economic viability of ancillary services provision by means of distributed ESSs. For the first functionality, an Exhaustive Research, a Genetic Algorithm and a Monte Carlo heuristic procedure have been coded and compared. For the latter functionality, an electric model of an ESS has been exploited in order to simulate a contribution to the primary frequency control and an ancillary market model has been developed in order to evaluate a multi service management of the storage; in particular frequency response and self-consumption logics have been evaluated.